Fìnansova baza vìdtvorennâ zemlì âk faktora virobnictva v umovah rinkovoï transformacìï ekonomìki UK - Panczyszyn, Stepan (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article compares the use of arable land in Ukraine and other countries. It presents issues concerning productivity and classification of land, including an analysis of financing sources for renewable properties of arable land both private and state-owned. The authors argue that land tax should be the main source of financial resources to be used for measures protecting arable lands. They also propose solutions to modernise state financial regulations with regard to land resources in Ukraine in view of investments in arable lands and forests falling threefold since 1991.
Keywords: gospodarka Ukrainy; użytkowanie gruntów ornych; klasyfikacja gruntów; podatek gruntowy